IMPLEMENTASI DATA MINING KLASIFIKASI KEPRIBADIAN ORANG-ORANG MENGGUNAKAN ALGORITMA NAÏVE BAYES - Sylvain Revata; Rino (Komunitas Dosen Indonesia, 2023)
Personality or personality comes from the word Persona, a word that refers to a mask or mask. This persona has the meaning of how a person looks in front of other people. In general, the personality of a person can be seen from how they appear and give an impression to the people around them. Therefore there are many personality types in a person, from these types it is difficult to predict someone. Because you have to be able to know the characteristics that exist in the types of personality. So with that made a data mining application to predict a person's personality type. Currently, the naïve Bayes classification algorithm is one method that is quite effective to be used in predicting future opportunities using previously existing data. This is because the naïve Bayes algorithm is a classification method that is easily understood by system designers and system users. The purpose of making this data mining application is to help people find out what personality type they have.